Automatic Weed Detection and Smart Herbicide Sprayer Robot - Y. Rajaa Vikhram, G; Agarwal, Rakshit; Uprety, Rohan; N.S. Prasanth, V (International Journal of Engineering and Technology, 2018)
The ordinary method for murdering weeds (unwanted plants) in a harvest manor is to shower herbicides all over the estate. This outcomes in defilement of the sustenance crops and furthermore the yield turns out to be less as a portion of the production plants pass on alongside the weeds. In this way, there is a requirement for a brilliant weed control framework. In this venture, a picture handling calculation is utilized to take pictures of the manor columns at consistent interims and after recognizing the weeds in the captured image, the weed killer chemical is showered specifically and just on the weeds. The herbicide is put away in a compartment fitted with water pump engines joined to shower spouts. After the weeds are recognized, a flag is signaled from Raspberry Pi to the motor driver IC governing the water pump motors to shower the chemicals over the unwanted vegetation.Â